PENGARUH PENGGUNAAN MEDIA CORONG HITUNG TERHADAP KETERAMPILAN BERHITUNG SISWA KELAS II SD NEGERI DI SALAH SATU KECAMATAN KELAPA - Sopiana Sopiana; Risnina Wafiqoh; M.Iqbal Arrosyad (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This research is prompted by the low numeracy skills in multiplication lesson with evidence of student learning outcomes that are still much below average. From this problem, the researcher used the counting funnel media on the numeracy skills of second-grade students of SD Negeri near of district Kelapa. This study aimed to determine the effect of using funnel counting media on students' counting skills in class II SD Negeri near of district Kelapa. This research is experimental research, namely quasi-experimental design, with a nonequivalent control design. The data collecting technique was a test. The data collection in this study is in the form of written essay questions. The sampling technique was a saturated sampling with a total sample of 42 students divided between the experimental class of 21 students and the control class of 21 students. The results of this study indicate that from the results of data analysis, the average value of the experimental class is 79.286 and the average value of the control class is 61.429. From the results of the hypothesis test, it was obtained that tcount is greater than ttable (5.546 > 2.021), that indicates the Ha was accepted. Thus it can be concluded that there is an effect of using the counting funnel media on the numeracy skills of second-grade students of SD Negeri near of district Kelapa